Ameaças da mineração de carbonaros marinhos e da energia eólica “offshore” na biodiversidade marinha: um ponto crítico para a economia azul - Paiva, Sandra Vieira (2023)
Marine ecosystems are essential for sustaining life on the planet, that provide numerous direct and indirect benefits. In this context, from the need for sustainable use of the oceans, and the planned expansion of activities in various marine sectors, the concept of Blue Economy emerged, which ensures the profitable and sustainable use of the resources provided by the sea. In this context, this thesis was organized into two chapters in the form of international scientific articles about two emerging activities in the marine environment that can directly impact the sustainable use of the oceans. The first chapter dealt with the mining of marine carbonates in the Western Southwest Atlantic, its current status, potential impacts and conservation actions. Marine carbonates are economically important due to their high concentration of calcium, being abundant in calcareous algae, mainly in the form of rhodoliths. Brazil has large deposits of marine carbonates, estimated at 2,1011 tons, with an exploration potential of 96,000 to 120,000 t/year. However, the growing interest in mining is threatening unique ecosystems such as rhodolith beds, as many active mining processes are in these areas. Currently, there is not enough scientific information to support the safe exploitation of these resources, in addition to the possible impacts on connectivity with other environments such as coral reefs. So for this activity to be better established, environmental policy actions are needed that prioritize the health of rhodolith banks. The second chapter dealt with the threats posed by the installation of offshore wind farms to tropical reef systems. These projects are also emerging in the scenario of the world's blue economy because they are renewable energy generation. The parks consist of the installation of wind turbines at sea, which have advantages due to high wind speeds and the possibility of high rates of land occupation. Currently, in Brazil, the installation of 66 wind farms is planned, with a total of 3,364 wind turbines installed at sea and a production potential of 48,410 MW (until November 2022). Of these, 18 parks are in the licensing process on the semi-arid coast of the equatorial Southwest Atlantic. Although it is a source of clean energy, these parks can affect reef systems in different ways, such as habitat destruction, burial, favoring the dispersal of invasive species such as sun coral and lionfish, etc. By overlaying spatial data, we detected, in an unprecedented way, that 83.3% of wind farm projects (15 enterprise) are expected to be installed in areas of high biological importance, such as reef systems. Many of the projects are also located less than 20 km away from areas where invasive species occur. The results of both articles highlight the need for urgent conservation action policies for the preservation of these marine ecosystems of high biological importance, such as studies of environmental impacts based on scientific evidence, adequate marine spatial planning, creation of new no-take marine protected areas and other conservation policies, in order to provide subsidies to discuss paths towards a blue economy in the South Atlantic.